Efektivitas Ekstrak Etanol Daun Sirih (Piper betle L.) dan Buah Mengkudu (Morinda citrifolia L.) Sebagai Alternatif Pengawet Tahu - Masnur Turnip, Rahel Asriani Pakpahan, Siti Khotimah, (Universitas Tanjungpura, 2015)
Tofu is one of the most popular food in Indonesian society. Tofu has a relatively short period of storage ranging from 1-2 days to be consumed, so it takes process of preservation in order to extend its storage life. One of the natural materials that could potentially serve as a natural preservative is the Piper betle leafand the noni fruit (Morinda citrifolia). This research aims to determine the concentration of each effective extract, the total number of bacterial colony and the organoleptic test results. The research was conducted from May until September 2014. It was an experimental design using the Completely Randomized Design. The concentrations of the extract used were 0%, 3%, 6% and 9% for each extract of Piper betle leaf and noni fruit. The results showed that the effective treatments in slowing down the process of decay were the Piper betle leaf extract (9%) and noni fruit extract (3%) with an average Total Plate Count (TPC)8.23x1010CFU/g dan 6.7x1010 CFU/g. Both extracts were able to maintain the storage life of tofu in room temperature for 3 days. The Piper betle leaf extract (9%) and noni fruit extract (3%) had a high value in the organoleptic parameter (aroma, texture, color and taste).